Evaluación de calidad de un servicio de voluntariado hospitalario en oncología: niveles de satisfacción de los pacientes de cáncer y sus familias - Fernández Sánchez, Belén; Martínez, Adoración (Psicooncología, 2017)
Objective and method: to evaluate the impact of the program for voluntary work at hospitals through the importance assigned, satisfaction level stated by users, and willingness to recommend the service. For this purpose, a satisfaction study was carried out in two phases: A quantitative study through personal interviews with semi-structured questionnaire and a qualitative study through open personal interviews. Results: 654 patients and family members took part. In the evaluation of volunteers, a rating of 9.3 is given by patients and 9.2 by family members, in a scale from 0 to 10. Seventy-seven percent of users is willing to recommend the volunteer service to others, achieving a clearly positive NPS index (+80). Users specially emphasize from volunteers their kindness and their respect for privacy (89% and 82% respectively) and provide an average rating of 9.2 and 9.4 in a scale of 0 to 10. Conclusions: Unanimous positive evaluation of the work by volunteers and great willingness to recommend the contact with volunteers is obtained. The increased use of the volunteer service is linked to better results achieved in the evaluation. Greater priority is given to the activity of visiting patients in hospitals to keep company and provide emotional support.The evaluation of the work performed by the volunteers is very positive, especially regarding kindness and respect for privacy. Rather than new specific requirements, users demand an increased dissemination of the service, more volunteers and extended service hours.